Glutamatergic Dysfunction in Skin-Picking Disorder Treatment of a Pediatric Patient With N-Acetylcysteine - Percinel, Ipek; Yazici, Kemal Utku (Lippincott Williams & Wilkins, 2014)
[Abstract Not Available]
Keywords: Obsessive-Compulsive Disorder; Acetyl Cysteine; Double-Blind; Placebo; Trichotillomania; Trial